Twin deficits or distant cousins? Why the distinction matters for banks in Kenya - Kiplangat Josea Cheruiyot; Jared Osoro (Kenya Bankers Association (KBA), 2025)
This paper seeks to determine the interaction mechanism between the domestic imbalance and the external imbalance in Kenya and why it matters for banks. Whenever an economy has is on a path of soaring fiscal and current account deficits like Kenya has been over the past decade, concerns on the implication in stability is palpable. The influence of the imbalance on banks' behaviour crucially depends on whether one deficit occasions the other in short order, hence the twin moniker, or not. If the two are twins, then the interaction between them has an influence on economic growth and consequently bank profitability. We demonstrate that the two deficits not only exert a direct influence on the economy but also indirectly affect financial sector performance via their impact on growth. While this finding endears itself to the twin deficit conclusion, the channel of influence is through the implication of the imbalances on stability more than it is through growth. We argue that while banks seldom miss the opportunity to maximise earnings from positions they take in both money and foreign exchange markets on the back of the twin deficits, policy makers ought to maintain a focus on how financial stability could be assured through regulation at the first level and pursuit of sustainability in each of the imbalances.
Keywords: 330